2022
DOI: 10.1038/s41420-022-01163-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated fibroblasts secreted exosomal miR-1290 contributes to prostate cancer cell growth and metastasis via targeting GSK3β

Abstract: Cancer-associated fibroblasts (CAFs) play crucial roles in mediating tumor growth and metastasis via transferring exosomes to neighboring cells, whereas the mechanisms by which CAFs regulate the tumorgenesis of prostate cancer (PC) remain largely unknown. In this study, CAFs and normal fibroblasts (NFs) were isolated from PC tissues and adjacent normal tissues, respectively. Exosomes (NFs-Exo and CAFs-Exo) were then isolated from the supernatant of NFs and CAFs. Next, the differentially expressed miRNAs (DEMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…In the TME, CDEs containing various miRNAs are internalized by recipient cells. This causes a reduction in mRNA expression as well as various phenotypic changes such as tumor progression, therapy resistance, metastasis, and metabolic reprogramming (Zhang et al 2020a , b , c ; Peng et al 2021a , b ; Qin et al 2019 ; Fang et al 2022 ; Wang et al 2022a , b ). Similarly, hnRNPA1 regulates the packaging of miR-196a into CDEs.…”
Section: Functional Features Of Cafs In Tumor Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the TME, CDEs containing various miRNAs are internalized by recipient cells. This causes a reduction in mRNA expression as well as various phenotypic changes such as tumor progression, therapy resistance, metastasis, and metabolic reprogramming (Zhang et al 2020a , b , c ; Peng et al 2021a , b ; Qin et al 2019 ; Fang et al 2022 ; Wang et al 2022a , b ). Similarly, hnRNPA1 regulates the packaging of miR-196a into CDEs.…”
Section: Functional Features Of Cafs In Tumor Biologymentioning
confidence: 99%
“…Exosomes are endosome-derived EVs that contain numerous signaling molecules, especially various non-coding RNAs. These RNAs play an important role in CAF-induced tumor cell stemness (Zhan et al 2021 ; Qu et al 2022 ; Hu et al 2015 ; Lin et al 2019 ; Liu et al 2020 ; (Wang et al 2022a , b ). circHIF1A (Zhan et al 2021 ) and cricN4BP2L2 (Qu et al 2022 ) contained in CDEs also regulate pro-tumor downstream signaling pathways by acting on tumor cells, thereby facilitating therapy resistance and tumor cell stemness.…”
Section: Functional Features Of Cafs In Tumor Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed earlier, several circulating RNAs are excellent as potential diagnostic markers of GC. Circulating exosomal miR-1290 has been reported to be upregulated in various malignant cancers, including GC [74], LUAD [75], epithelial ovarian cancer [76], and PCa [77]. Kumata et al observed that the miR-23b in exosomes from the plasma of GC patients was significantly lower than that of the healthy donors [78].…”
Section: Gastric Cancermentioning
confidence: 99%
“… [ 190 ] miR-1290 Prostate cancer Promote EMT and metastasis via targeting GSK3β expression in cancer cell. [ 197 ] miR-146a-5p Prostate cancer Promote cancer metastasis. Treatment of Dihydrotestosterone (DHT) decrases miR-146a-5p in CAF-derived EVs and attenuate cancer promoting function.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%